Protection of Religious Minorities under Islamic Legal System and International Law of Human Rights - Mostafa Fazaeli; null null; ثریا اسدی (پژوهش تطبیقی حقوق اسلام و غرب, 2017)
This article, through a descriptive-analytic method and on a library-based approach and by means of analyzing the protection of religious minorities under Islamic legal system in one side and International Minority Protection Law (IMPL) in the other side, aims to illustrate the relation between these two systems. Religious Minorities have been the first type of these groups enjoying international legal protection and it was after the occurrences such as French Revolution and American Independence that protection has been on rather secular basis. Religious minorities have been a serious Islamic concern from the outset of its revelation. Thereupon, through taking into account the requirements of time and place could be a remarkable pattern in protecting minorities. States, by means of human rights obligations, have a duty to respect, protect and fulfill religious rights of minorities under International Law; meanwhile, in Islamic system and under Tribute Contract, Islamic State shall protect minorities and respect and ensure their political, civil, economic, social and judicial rights. As a result, by comparison with International Human Rights Law, it seems that Tribute Contract, at least in a faith community, is more capable in realization and assurance of the rights of religious minorities.